2015
DOI: 10.1080/19648189.2015.1036129
|View full text |Cite
|
Sign up to set email alerts
|

Shear behaviour and load capacity of short reinforced concrete beams exposed to chloride environment

Abstract: The effect of corrosion of reinforcement on the behaviour of deep, reinforced concrete beams was investigated. Long-term corrosion (27 years) in an accelerated climate process using a chloride environment close to natural corrosion resulted in a high level of heterogeneous loss of cross section on both longitudinal reinforcement and transversal reinforcement (stirrups). Control beams of the same age kept in a non-aggressive environment were also tested as controls. Tension reinforcement did not have special an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The 19 RC beams were taken from 13 different collaborative groups who were involved in the project (Castel et al. , 2000; Dang et al. , 2016; Dang and François, 2014; François et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 19 RC beams were taken from 13 different collaborative groups who were involved in the project (Castel et al. , 2000; Dang et al. , 2016; Dang and François, 2014; François et al.…”
Section: Methodsmentioning
confidence: 99%
“…The data from Laboratoire des Mat eriaux et Durabilit e des Constructions (LMDC) were obtained from a long-term experimental program that started in 1984 in Toulouse, France. The 19 RC beams were taken from 13 different collaborative groups who were involved in the project (Castel et al, 2000;Dang et al, 2016;Dang and François, 2014;François et al, 2013;Khan et al, 2012Khan et al, , 2014Kreit et al, 2011;Vidal et al, 2007;Yu et al, 2015;Zhang et al, 2009;Zhu et al, 2013Zhu et al, , 2015Zhu and François, 2016). The beams have undergone a series of continuous spraying and wetting-drying cycles for 3-27 years before subjecting them to a three-point loading system.…”
Section: Data Gatheringmentioning
confidence: 99%
“…The four tested RC beams were compared to other two beams; one is corroded A2CL2-A and the other is control tested by Dang et al (31), Figure 5 shows the load-deflection curves for all short beams tested experimentally. The shear strengthening increased the shear capacity for the control beams, while the response of the corroded beams due to shear strengthening depends on the pattern and the intensity of steel corrosion.…”
Section: Ultimate Load Capacity and Modes Of Failurementioning
confidence: 99%
“…Load-deflection curves for all beamsThe difference in the yielding capacity of the shear repaired control beam A1T-SB and the shear repaired corroded beam A1CL3-SB refers to the 12% loss in cross section found at the middle of the corroded beam A1CL3-SB (the load-induced crack occurs at mid-span), while the decrease in the yielding capacity for non-shear repaired corroded beam A2CL2-A in comparison with non-shear repaired beams (Control, A1T-B and A1CL3-B) refers to the 10% loss in cross section found at the edge of the corroded beam A2CL2-A (the same edge of diagonal shear crack)(31).Experimental results showed also that shear strengthening with NSM CFRP rods technique changed the mode of failure from diagonal crack failure close to support due to slipping of tensile re-bars at anchorage (for non-shear-repaired beams A1T-B and A1CL3-B), to large flexural crack at mid span followed by concrete crushing (for shear-repaired beams A1T-SB and A1CL3-SB) as shown infigure 6. Experimental modes of failure for all tested beams It is also noteworthy that for shear-repaired beams A1T-SB and A1CL3-SB, many splitting cracks occurred at the mid-way of the beam's width as shown in figure 7 , these splitting cracks were clear to notice at the bottom of the beam and at the beams edges near the supports.…”
mentioning
confidence: 99%
“…It has also been observed that corrosion of stirrups leads to the degradation of confined performance of core concrete [38]. Many studies have shown that the contribution of corrosion stirrups to the bearing capacity and ductility of beams [39][40][41] or columns [42][43][44] is reduced due to the corroded stirrups, which fails in confining the core concrete. Therefore, the weakening effect of confinement to the core concrete due to corroded stirrups should also be considered in numerical simulation [37].…”
mentioning
confidence: 99%